A new species of the genus Termitodiellus Nakane, 1961 (Coleoptera: Scarabaeidae: Aphodiinae) from Vietnam - Minkina, Łukasz; Byk, Adam; Kamiński, Marcin Jan (Zootaxa, 2026)
A new Termitodiellus Nakane, 1961 species from Vietnam is described and illustrated: Termitodiellus bielawskipisars-kiorum Minkina, Byk & Kamiński, sp. nov. New distributional records for Termitodiellus luzonensis (Howden, 1995) are provided. The taxonomic complexities of Termitodiellus are briefly discussed in the light of related genera and an updated key for species identification is presented. Finally, a map of the distribution of all currently known Termitodiellus species is provided.